Penggredan pada ruang topologi kabur - Md Tap, Abu Osman; Wahab, Abd Fatah (Penerbit Universiti Kebangsaan Malaysia, 1999)
Hazra et al. introduced a new definition of fuzzy topology via the gradation of openness (closedness) for fuzzy subset of X and studied the gradation preserving map. In this paper, we further study the concepts of induced gradation, gradation contraction map, gradation expansion map, gradation fixing map and the gradation preserving map on a fuzzy topological space.